ANALISIS KESTABILAN LERENG DENGAN MENGGUNKAN METODE PROBABILITAS PADA PENAMBANGAN BATUGAMPING DI PT. CALDOMILL INDONESIA KABUPATEN GUNUNGKIDUL, PROVINSI D.I YOGYAKARTA - Rofa Dzulfikri Bulopa (Retii, 2022)
Indonesia is a country that is rich in natural resources, especially the content of certain types of non-metallic minerals so that it is one of the very large potentials. Gunungkidul Regency has a large potential for minerals, especially industrial minerals scattered in several places. PT. Caldomill Indonesia is a limestone mining located in Sidorejo Village, Ponjong District, Gunungkidul Regency, Yogyakarta Special Region Province. This company has been engaged in the production of limestone flour since 2017 and has excavation slopes with slopes ranging from 7 meters to 22 meters while the slope angle is 72° to 86° which is quite steep. The purpose of this study is to analyze and calculate the value of the safety factor on the condition of the stability of the limestone slopes, and analyze the condition of the slope stability of the company based on the probability of landslides. This research uses probability method in limestone mining at PT. Indonesian Caldomill in Gunungkidul Regency. The results of the slope stability analysis with Monte Carlo simulations obtained a landslide probability value of 15-20% and a maximum FK of 1.273 and a minimum FK of 0.480 including safe based on the standardization of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018 PK 12-50% and FK >1.1 (safe). The results of the Stereographic Projection analysis show that the slopes of the study site have a potential for wedge landslides of 10% and overturning of 10%. Based on the results of rock mass classification using four methods to show the slopes at the research site have good conditions. In the calculation of the RMR obtained a value of 67 rock mass II (strong). For the calculation of SMR obtained a value of 67, rock mass class (II) is good and stable with a landslide probability of 20-40%. While the GSI value is obtained from the SCR parameter of 9 and SR 60 and the condition of the Bloky structure. And the results of the Q-Slope show that the rock slope is in a stable condition at 13.07 at a slope of 72o.